2016
DOI: 10.3847/0004-6256/152/4/84
|View full text |Cite
|
Sign up to set email alerts
|

A High-Resolution Multiband Survey of Westerlund 2 With the Hubble Space Telescope. Ii. Mass Accretion in the Pre-Main-Sequence Population

Abstract: We present a detailed analysis of the pre-main-sequence (PMS) population of the young star cluster Westerlund 2 (Wd2), the central ionizing cluster of the H II region RCW 49, using data from a high resolution multi-band survey with the Hubble Space Telescope. The data were acquired with the Advanced Camera for Surveys in the F 555W , F 814W , and F 658N filters and with the Wide Field Camera 3 in the F 125W , F 160W , and F 128N filters. We find a mean age of the region of 1.04 ± 0.72 Myr. The combination of d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
(160 reference statements)
1
13
0
Order By: Relevance
“…It will also give insight into the evolution and distribution of disk-bearing objects throughout the cluster. Observations (e.g., De Marchi et al 2011;Zeidler et al 2016a) hint that the close proximity to the OB-star population accelerates mass accretion processes in protostellar disks, leading to a faster disk dispersal, and eventually hinders planet formation, confirming various theoretical studies (e.g., Clarke 2007;Anderson et al 2013;Winter et al 2020). JWST will also allow us to map the gradual evolution of the gas and dust within the star-forming region as a function of its ionising stellar population.…”
Section: Feedback Processes and Stellar And Gas Dynamicssupporting
confidence: 60%
See 1 more Smart Citation
“…It will also give insight into the evolution and distribution of disk-bearing objects throughout the cluster. Observations (e.g., De Marchi et al 2011;Zeidler et al 2016a) hint that the close proximity to the OB-star population accelerates mass accretion processes in protostellar disks, leading to a faster disk dispersal, and eventually hinders planet formation, confirming various theoretical studies (e.g., Clarke 2007;Anderson et al 2013;Winter et al 2020). JWST will also allow us to map the gradual evolution of the gas and dust within the star-forming region as a function of its ionising stellar population.…”
Section: Feedback Processes and Stellar And Gas Dynamicssupporting
confidence: 60%
“…While X-ray observations require space missions (e.g., Chandra or XMM-Newton), the optical and NIR observations can also be obtained from the ground, and with extreme AO even at similar spatial resolutions as HST provides. Combining these broad-band observations with narrow-band observations such as the Hα or Paβ filter allows to detect pre-main sequence stars with active mass accretion (e.g., De Marchi et al 2011;Beccari et al 2015;Zeidler et al 2016a;Kalari 2019) revealing protoplanetary disks. NUV and FUV photometry and spectroscopy from space is necessary to study and classify the most massive OB-stars.…”
Section: Observing Young Star-forming Regionsmentioning
confidence: 99%
“…As a consequence of their large integrated masses, the rich stellar populations of Wd1 and the Arches and Quintuplet clusters provide a unique opportunity to study the post-main sequence evolution of stars with M init ∼ 20 M to 120 M in the ∼2−5 Myr window (Clark et al 2018b(Clark et al , 2019b. Inclusion of clusters such as NGC 3603 or Westerlund 2 would extend this investigation to relatively unevolved very massive stars (∼1 Myr and 80 M ; Melena et al 2008;Zeidler et al 2016;Bonanos et al 2004;Schnurr et al 2008). Conversely, older aggregates such as Berkeley 51 and 55 and the RSG dominated clusters at the base of the Scutum-Crux arm (∼10−50 Myr; Lohr et al 2018b;Davies et al 2007;Clark et al 2009) permit the lifecycle of stars of initial masses down to ∼8 M -delineating the onset of core-collapse -to be explored.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 97%
“…Using the HST Advanced Camera for Surveys (ACS; filters F555W, F658N and F814W) and the Wide Field Camera (WFC3) IR channel (filters F125W, F128N, and F160W, PI Nota, GO-13038) we found that the cluster consists of two nearly coeval clumps (Zeidler et al 2015), and that is mass segregated (Zeidler et al 2017). Following the same approach described in De Marchi et al (2010), we identified a rich population of PMS stars with Hα excess, that are likely still accreting material from their circumestellar disks (Zeidler et al 2016) The paper is organized as follows. In Section 2 we present the data, describe how we created the reference frame and performed the photometric reduction.…”
Section: Introductionmentioning
confidence: 59%